A Paradoxical Effect of Interleukin-32 Isoforms on Cancer - Shim, Saerok; Lee, Siyoung; Hisham, Yasmin; Kim, Sinae; Nguyen, Tam T.; Taitt, Afeisha S.; Hwang, Jihyeong; Jhun, Hyunjhung; Park, Ho-Young; Lee, Youngmin; Yeom, Su Cheong; Kim, Sang-Yeob; et al. (Frontiers in Immunology, 2022)
IL-32 plays a contradictory role such as tumor proliferation or suppressor in cancer development depending on cancer type. In most cancers, it was found that the high expression of IL-32 was associated with more proliferative and progression of cancer. IL-32β was found mostly in different types of cancer and associated with cancer expansion. This observation is legitimate since cancer exhibits some hypoxic environment and IL-32β was known to be induced under hypoxic conditions. However, IL-32θ interacts directly with protein kinase C-δ reducing NF-κB and STAT3 levels to inhibit epithelial-mesenchymal transition. This effect could explain the different functions of IL-32 isoform in cancer. Pro- or anti-tumor activity depends on obesity, gender, age relating to IL-32 have not been studied yet. However, obesity-related IL-32 regulation indicated the role of IL-32 in cancer metabolism and inflammation. IL-32 specific direction in cancer therapy is difficult to conclude. In this review, we address that the paradoxical effect of IL-32 on cancer is attributed to the dominant isoform, cancer type, tumor microenvironment, and genetic background.